Adaptive Design Evaluator: A Co‐Assessment Tool for Early Planning Stages - Julia Forster; Stefan Bindreiter; Sanela Pansinger (Urban Planning)
Many municipalities face intense development pressures, challenging them to ensure spatial sustainability. Current assessment methods are designed for larger projects and are often time‐consuming and resource intensive. Certification systems like ÖGNI, DGNB, LEED, and BREEAM use detailed but rigid criteria, making them unsuitable for dynamic co‐creation processes. Smaller projects lack tools to visualize development impacts or generate tailored sustainability checklists. This article introduces the Adaptive Design (AD) Evaluator, an innovative, step‐by‐step methodology for sustainable impact assessment in building and planning projects. The AD Evaluator involves public and private stakeholders in a co‐creation process, integrating questionnaires, system dynamics models and spatial analysis to efficiently assess project interventions. The results are presented visually, enabling adaptable, resource‐efficient planning across four sustainability pillars. This approach supports quick assessments, offering perspectives from both developers and system owners (e.g., municipalities) and minimizes deviations from sustainable outcomes. The innovation of this approach lies in the introduction of the first conceptual scenario assessment generator for qualitative sustainability inventory and impact assessment in planning practice. The AD Evaluator supports the co‐design of structured yet flexible planning pathways for sustainable and adaptive urban environments by mapping and visualizing the impacts of planning in a jointly negotiated framework.